Utopía estética. “hacia la unidad del globo” (2020)
The present text aims to expose the notion of “aesthetic utopia” from the philosophical thought of René Schérer, understanding it as a power (puissance) that can change reality, transform it (in the sense of revolution), proof of this we will see, in particular in the proposal for an “aesthetic-passionate education”. Because of this, the text has been organized in two parts: the first, it will seek to show the foundations of “aesthetic utopia” in the thought of René Schérer, also addressing some of the key notions that give shape to this utopia, such as utopia-philosophy and passionate aesthetics. In the second part, it will be sought to account, from all this "constellations" of notions, the way in which “aesthetic utopia” is conceived in its connection with “desire”.